2020
DOI: 10.1016/j.ijfoodmicro.2019.108361
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequence analysis of antimicrobial resistance genes, multilocus sequence types and plasmid sequences in ESBL/AmpC Escherichia coli isolated from broiler caecum and meat

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…The isolates in the present study carried AMR genes conferring resistance against critically important antimicrobials (WHO, 2019), including aminoglycosides, third-and fourthgeneration cephalosporins, macrolides, and quinolones, whereas no macrolide or PMQR was found in the isolates recovered from Finnish poultry production in the earlier study (Oikarainen et al, 2019). Another study of broilers at slaughterhouses found only limited sulfonamide resistance in addition to ESBL/AmpC with no other resistance genes in broiler meat and cecum samples (Päivärinta et al, 2020).…”
Section: Discussionmentioning
confidence: 47%
“…The isolates in the present study carried AMR genes conferring resistance against critically important antimicrobials (WHO, 2019), including aminoglycosides, third-and fourthgeneration cephalosporins, macrolides, and quinolones, whereas no macrolide or PMQR was found in the isolates recovered from Finnish poultry production in the earlier study (Oikarainen et al, 2019). Another study of broilers at slaughterhouses found only limited sulfonamide resistance in addition to ESBL/AmpC with no other resistance genes in broiler meat and cecum samples (Päivärinta et al, 2020).…”
Section: Discussionmentioning
confidence: 47%
“…The presence of ESBL-MDR pathogens is a serious health problem due to the limited available drug regimens for treatment. Food producers, including farms and slaughterhouses, are important transmission sources of antibiotic resistance [39,40].…”
Section: Plos Onementioning
confidence: 99%
“…The plasmids were detected in E. coli isolates from chickens, chicken meat, and humans in the Netherlands and Switzerland. The majority of E. coli isolates from chickens harbored bla CMY-2 -positive IncK plasmids in Denmark, the Netherlands, Norway, Sweden, and Finland (18,22,(31)(32)(33). Furthermore, the plasmids from chickens, chicken meat, and humans in Switzerland were identical to each other, with more than 95% identity (34).…”
Section: Figmentioning
confidence: 99%